A new apterous species of Chevron Crickets Anabropsis Rehn, 1901 from Yunnan, China (Orthoptera: Anostostomatidae: Anabropsini) - Yin, Zixu (Zootaxa, 2025)
Anabropsis (Spinanabropsis) zeluni sp. nov. is described from Yunnan, China. The new species is characterized by an hourglass-shaped marking on the pronotum. A key to all apterous (or micropterous) subgenera of Anabropsis from China is provided. Type specimens are deposited in Museum of Biology, East China Normal University.